벡터 성분 연산

Jmnote (토론 | 기여)님의 2013년 4월 21일 (일) 16:42 판 (→‎개요)

1 개요

벡터 성분 연산
[math]\displaystyle{ (a_1, a_2)+(b_1, b_2)=(a_1+b_1, a_2+b_2) }[/math]
[math]\displaystyle{ (a_1, a_2)-(b_1, b_2)=(a_1-b_1, a_2-b_2) }[/math]
[math]\displaystyle{ m(a_1, a_2)=(ma_1,ma_2) }[/math]
[math]\displaystyle{ (a_1, a_2, a_3)+(b_1, b_2, b_3)=(a_1+b_1, a_2+b_2, a_3+b_3) }[/math]
[math]\displaystyle{ (a_1, a_2, a_3)-(b_1, b_2, b_3)=(a_1-b_1, a_2-b_2, a_3-b_3) }[/math]
[math]\displaystyle{ m(a_1, a_2, a_3)=(ma_1,ma_2, ma_3) }[/math]

2 같이 보기

문서 댓글 ({{ doc_comments.length }})
{{ comment.name }} {{ comment.created | snstime }}